2018
DOI: 10.1590/s1679-45082018ao4225
|View full text |Cite
|
Sign up to set email alerts
|

What are the most frequent diagnoses in adolescence? The reality of an Adolescent Medicine Clinic

Abstract: ObjectiveTo characterize the care flow and the primary diagnoses of an Adolescent Medicine Clinic.MethodsA retrospective descriptive study, with analysis of clinical processes of adolescents (10-18 years) seen at the Adolescent Medicine Clinic, from January 2006 to December 2013. The following variables were analyzed: sex, age, number of visits, referring service and primary diagnoses according to the International Statistical Classification of Diseases and Related Health Problems. As to the variable age, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
(27 reference statements)
0
3
1
2
Order By: Relevance
“…(10) Contrary to what is found in other national studies related to adolescent medicine consultation, in this study, male prevalence was higher, (2,3,11) and literature demonstrates well the fact that boys generally seek health care less. (1,(11)(12)(13)(14) This study result can be interpreted taking into consideration that we were able to reach the group of boys through the application of the PSUA tool, which allowed us to invite them to a consultation in a school setting.…”
Section: ❚ Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…(10) Contrary to what is found in other national studies related to adolescent medicine consultation, in this study, male prevalence was higher, (2,3,11) and literature demonstrates well the fact that boys generally seek health care less. (1,(11)(12)(13)(14) This study result can be interpreted taking into consideration that we were able to reach the group of boys through the application of the PSUA tool, which allowed us to invite them to a consultation in a school setting.…”
Section: ❚ Resultscontrasting
confidence: 78%
“…Despite the apparent concern in controlling their weight, adolescents are at nutritional risk due to the dietary mistakes they make, and the high percentage of body fat that many present. (21) In a nationwide study, (11) eating disorders were the most frequent mental disorders in consultation. Perhaps the fact that, in the present study, the physician conducted the interview making it more directed and detailed, explains the difference in responses between completion of the questionnaire and the data obtained at the medical appointment.…”
Section: ❚ Discussionmentioning
confidence: 99%
“…Being physically active benefits mental, physical, and social health [ 5 , 16 ], yet, existing evidence suggests a global pandemic of physical inactivity [ 4 ]. Abreu et al [ 17 ], in a study evaluating the reasons for medical consultations by adolescents, identified that most of the diseases diagnosed in this population have a strong behavioral and social component, with emphasis on mental illness and obesity. Such findings highlight the need for a global approach to adolescents, valuing healthy lifestyle practices [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Um estudo que teve como objetivo conhecer os principais diagnósticos em um ambulatório geral que realiza consultas médicas e de enfermagem a adolescentes com problemas de saúde, entre 10 e 18 anos de idade, em Portugal, evidenciou que os transtornos mentais e de comportamento foram os mais prevalentes entre o grupo das meninas e entre o grupo dos adolescentes de 14 a 18 anos. As doenças mentais representaram o segundo grupo de diagnósticos mais prevalentes entre os adolescentes acompanhados por este ambulatório, sinalizando a importância de oferta de cuidado em saúde específico para esta população (12) .…”
Section: Introductionunclassified